The Discovery of Forensics Chemistry Latent Fingerprints: An Article Review - Eamd Yousif; Dina Ahmed; Hanan Ibraheem; Rahimi Yusop; Khalid Zainulabdeen; Amamer Redwan (Indonesian Journal of Chemical Education, 2024)
Forensic chemistry distinguishes itself from other branches of chemical sciences by the necessity to cater to the requirements of both the scientific and legal communities. Its research, application, and presentation are uniquely geared towards meeting the needs of these two domains. Consequently, forensic chemistry research is inherently practical and derived, emphasizing metrology (the science of measurement) and validation. Forensic chemistry has evolved beyond its initial analytical origins and now encompasses a broader range of chemical sciences. As the field expands, established forensic practices are being reevaluated, extending beyond drug analysis and toxicology to encompass diverse areas such as combustion chemistry, materials science, and pattern evidence. Chemistry has been used more and more to help with criminal investigations and forensic chemistry has become an important topic of study for students at all levels of education. The excitement of carrying out chemical tests is increased with the chance to explore a criminal incident. Both educators and students are consistently intrigued by the prominence of chemistry in crime scene investigations depicted in television shows. Fingerprint analysis, a key component of forensic science, has been adapted for every educational level. From elementary school students creating fingerprints with ink to the exciting (and messy) activity of revealing latent fingerprints through dusting, educators have found engaging ways to incorporate forensic science lessons. Superglue, readily available commercially, allows anyone interested to show its capabilities for detecting latent prints. Forensic science or forensic chemistry courses in high school and postsecondary education often include experiments involving the revelation of latent fingerprints. Latent fingerprints are formed when a person touches a surface, leaving behind a nearly transparent chemical residue that mirrors their unique skin ridge patterns. Latent fingerprints are likely to be left on surfaces every time you contact or grab them. To improve the contrast between the fingerprint residue and the surface it has been applied on, many methods have been established. Abundant and resilient, latent prints are unintentionally left behind on the surfaces you touch daily. Specialized techniques can reveal many of these latent prints, highlighting their potential significance in forensic investigations.